Estrategias para disminuir la evasión en el recaudo de impuestos en el departamento del Chocó. - Asprilla Abadia, Jhonny James (Universidad Antonio Nariño, 2021)
This research project analyzes the phenomenon of the concept of evasion, including the main causes or origin of this. Finally, the information obtained is analyzed and concludes with the identification of the main factors that affect e›’asion, its economic, social and cultural effects, finding that the department's tax revenues are quite low and not very significant within its income budget. ; and insufficient to finance the department's operating expenses. We will propose some strategies or measures that the department must take to reduce tax ev’asion and thus begin to strengthen departmental revenues.